2012
DOI: 10.1152/japplphysiol.00960.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessments of the knee joint biomechanics by using pendulum test in adults with Down syndrome

Abstract: In this study, we assessed kinematics and viscoelastic features of knee joint in adults with Down syndrome (DS) by means of the Wartenberg pendulum test. This test allows the measuring of the kinematics of the knee joint during passive pendular motion of leg under the influence of gravity. In addition, by a combination of kinematic and anthropometric data, pendulum test provides estimates of joint viscoelastic properties by computing damping and stiffness coefficients. To monitor the occurrences of muscle acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…During the unpredictable condition of the present study, almost all the latencies of the compensatory responses recorded in the knee extensor and flexor muscles of healthy participants fell below either 50 or 100 ms (VL: 94,2 %; RF: 95,5 %; BF: 77,3 %) and may then be considered short-and long-latency reflexes (Matthews 1991;Casabona et al 2012). Conversely, almost all the latencies of the knee extensor and flexor muscles recorded in patients with ACLR fell above either 50 or 100 ms (VL: 90,9 %; RF: 90,9 %; BF: 93,9 %) and may then be considered long-latency 13 reflexes or voluntary responses (Pruszynski and Scott 2012;Valle et al 2013).…”
Section: Compensatory Postural Responses To Unpredictable Perturbationsmentioning
confidence: 61%
See 1 more Smart Citation
“…During the unpredictable condition of the present study, almost all the latencies of the compensatory responses recorded in the knee extensor and flexor muscles of healthy participants fell below either 50 or 100 ms (VL: 94,2 %; RF: 95,5 %; BF: 77,3 %) and may then be considered short-and long-latency reflexes (Matthews 1991;Casabona et al 2012). Conversely, almost all the latencies of the knee extensor and flexor muscles recorded in patients with ACLR fell above either 50 or 100 ms (VL: 90,9 %; RF: 90,9 %; BF: 93,9 %) and may then be considered long-latency 13 reflexes or voluntary responses (Pruszynski and Scott 2012;Valle et al 2013).…”
Section: Compensatory Postural Responses To Unpredictable Perturbationsmentioning
confidence: 61%
“…Since long-loop circuits are involved, this process can take place, thus allowing the sensory signal to be specifically associated to the task and the motor response to be adapted instantaneously to the actual circumstances (Lewis et al 2006;Kurtzer et al 2008;Pruszynski and Scott 2012;Pruszynski et al 2011;Casabona et al 2012;Valle et al 2013).…”
Section: Compensatory Postural Responses To Unpredictable Perturbationsmentioning
confidence: 99%
“…This means that the pennation angle may be considered the morphological correlation of the phasic activation of the RF after the leg release. In previous papers we showed that this muscle activity appears when persons with DS pass from adolescence to the adult age, indicating a possible functional compensation for the inherent ligaments laxity [13, 14]. Thus, changes in pennation angle may be a structural sign associated with specific functional adaptations occurring in DS when rapid muscle activations are required.…”
Section: Discussionmentioning
confidence: 84%
“…The analysis of the knee motion was performed using the pendulum test (for an extensive description of this procedure see Casabona et al, [13]). By means of this technique, angle amplitude variations at the knee were recorded by an electrogoniometer placed on the lateral side of the tested limb.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation